Design, synthesis and antitumor evaluation of novel pyrazolo[3,4-d]pyrimidines incorporating different amino acid conjugates as potential DHFR inhibitors - Ibrahim M. Salem; Samia M. Mostafa; Ismail Salama; Osama I. El-Sabbagh; Wael A. H. Hegazy; Tarek S. Ibrahim (Taylor & Francis Group, 2023)
The present study aimed to investigate the antitumor effect of simultaneous inhibition of dihydrofolate reductase (DHFR) enzyme. We designed some novel pyrazolo[3,4-d]pyrimidines bearing different amino acid conjugates as efficient antifolate agents attributable to their structural similarity with methotrexate (MTX) and MTX-related antifolates. All compounds were tested to screen their enzymatic inhibition against DHFR compared with the reference drug MTX and for their in vitro antitumor cytotoxicity against six MTX-resistant cancer cell lines. The flow cytometry indicated that the most potent compound 7f arrested MCF-7 cells in the S-phase and induced apoptosis. Western blot for visualisation proved the ability of compound 7f to induce the expression of proapoptotic caspases and Bax proteins in MCF-7 breast cancer cell line beside its ability to diminish the expression of antiapoptotic Bcl-2 protein. Molecular modelling studies concluded that compound 7f displayed better binding energy than that of the normal ligand MTX.